Young carers’ perspectives on navigating the healthcare system and co-designing support for their caring roles: a mixed-methods qualitative study - Jill I Cameron; Shoshana Hahn-Goldberg; Karen Okrainec; Marianne Saragosa; Yona Lunsky; Isabelle Caven; Susan Bookey-Bassett; Kristine Newman (BMJ Open)
Objectives Despite young carers (YCs) providing regular and significant care that exceeds what would normally be associated with an adult caregiver, we need to learn more about their experience interacting with the healthcare system. The primary study aims were to (1) describe YC experiences in interacting with the healthcare system and (2) identify types of support YC recognise as potentially helpful to their caring role.Design and setting A mixed-methods qualitative study was conducted between March 2022 and August 2022, comprising two phases of (1) semi-structured interviews and focus groups with YCs living in the community to confirm and expand earlier research findings, and (2) a co-design workshop informed by a generative research approach. We used findings from the interviews and focus groups to inform the brainstorming process for identifying potential solutions.Results Eight YCs completed either a focus group or an interview, and four continued the study and participated in the co-design activity with 12 participants. Phase 1 resulted in three overarching themes: (1) navigating the YC role within the healthcare system; (2) being kept out of the loop; and (3) normalising the transition into caregiving. Phase 2 identified two categories: (1) YC-focused supports and (2) raising awareness and building capacity in the healthcare system.Conclusion Study findings revealed the critical role that YCs play when supporting their families during pivotal interactions in the healthcare system. Like their older caregiver counterparts, YCs struggle to navigate, coordinate and advocate for their family members while juggling their needs as they transition from adolescence to adulthood. This study provides important preliminary insights into YCs encountering professionals, which can be used to design and implement national support structures.